2013
DOI: 10.1117/1.oe.52.9.091804
|View full text |Cite
|
Sign up to set email alerts
|

Development of sensitive long-wave infrared detector arrays for passively cooled space missions

Abstract: Abstract. The near-earth object camera (NEOCam) is a proposed infrared space mission designed to discover and characterize most of the potentially hazardous asteroids larger than 140 m in diameter that orbit near the Earth. NASA has funded technology development for NEOCam, including the development of long wavelength infrared detector arrays that will have excellent zodiacal background emission-limited performance at passively cooled focal plane temperatures. Teledyne Imaging Sensors has developed and deliver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Future generations of spacebased IR telescopes using new large-format detectors (e.g. McMurtry et al 2013) will further improve our understanding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future generations of spacebased IR telescopes using new large-format detectors (e.g. McMurtry et al 2013) will further improve our understanding.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the WISE mission included four 1024 2 detector arrays, each with 18 µm pixels (Mainzer et al 2005). Recent developments include the fabrication of megapixel mid-IR detectors capable of operating at higher temperatures, which will ease the burden on cryogenic systems for future missions (McMurtry et al 2013).…”
Section: The Missionsmentioning
confidence: 99%
“…12 In order to remove the substrate, the volume between the silicon multiplexer and the detector must be epoxy backfilled, because the light-sensitive HgCdTe layer is thin (∼10 μm). McMurtry et al 3 investigated the effect of epoxy backfill on the substrate-intact LWIR devices and showed that it did not adversely affect the dark current, well depth, quantum efficiency, or noise although an increase in interpixel capacitance was noted.…”
Section: Motivationmentioning
confidence: 99%
“…Laboratory testing of several arrays grown on an 800-μm CdZnTe substrate, and hybridized to an H1RG multiplexer, demonstrated that the resulting detector arrays met all NEOCam requirements (see Table 1) for dark current, quantum efficiency, well depth, and noise. 3 Short-wave infrared (SWIR) and mid-wave infrared (MWIR) HgCdTe detector arrays utilizing the same multiplexer, or the same family of multiplexers in a larger format, have been or will be employed in other space missions, including the Orbiting Carbon Observatory 2, the Wide-field Infrared Survey Explorer (WISE), the Hubble Space Telescope's (HST) Wide Field Camera 3, Euclid, and JWST. 2,4,[5][6][7] Detector arrays flown in space must be robust against cosmic ray (CR) hits; therefore, we subjected the arrays from 12 to 63 MeV protons to determine the magnitude of the responses.…”
mentioning
confidence: 99%
“…One key outcome of the assessment phase was the identification of an MCT detector with TRL approaching 5 that worked up to 11 μm at an operating temperature of~40 K. This device has been developed by Teledyne working with JPL and University of Rochester in the frame of a Phase A study for NEOCam (a Near Earth Object detection mission being studied for a potential 2018 launch [13]). This meant that EChO would have had an all MCT solution with operating temperatures no lower than 28 K (somewhat lower than the NEOCam baseline due to the desired lower dark current in the EChO application).…”
Section: Detector Systemsmentioning
confidence: 99%